2015
DOI: 10.1002/etc.3034
|View full text |Cite
|
Sign up to set email alerts
|

Some arguments in favor of a Myriophyllum aquaticum growth inhibition test in a water–sediment system as an additional test in risk assessment of herbicides

Abstract: The present study compares the practicability, reproducibility, power, and sensitivity of a Myriophyllum aquaticum growth inhibition test in a water-sediment system with the recently accepted Myriophyllum spicatum test in an equivalent testing system and the standard Lemna sp. test. Special consideration was given to endpoints based on M. aquaticum control plant growth and variability of relative growth rate and yield: shoot length, fresh weight, dry weight, and root weight. Sensitivity analysis was based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
2
9
1
Order By: Relevance
“…The number of analyzed pollutants in sediments tested in this study was limited; hence, plant growth could have been affected by the presence of non-identified pollutants, as well. Plant protection products could have been key toxicants responsible for observed growth inhibitions, bearing in mind the land use patterns in the vicinity of selected water bodies and high sensitivity of selected species to herbicides [41]. Similarly to our study, Feiler et al [42] recorded insignificant M. aquaticum growth inhibition in a highly contaminated sample, growth stimulation in slightly to moderately contaminated samples and high inhibition in the slightly contaminated sample.…”
Section: Test Of Natural Sedimentssupporting
confidence: 85%
See 1 more Smart Citation
“…The number of analyzed pollutants in sediments tested in this study was limited; hence, plant growth could have been affected by the presence of non-identified pollutants, as well. Plant protection products could have been key toxicants responsible for observed growth inhibitions, bearing in mind the land use patterns in the vicinity of selected water bodies and high sensitivity of selected species to herbicides [41]. Similarly to our study, Feiler et al [42] recorded insignificant M. aquaticum growth inhibition in a highly contaminated sample, growth stimulation in slightly to moderately contaminated samples and high inhibition in the slightly contaminated sample.…”
Section: Test Of Natural Sedimentssupporting
confidence: 85%
“…When methods in ecotoxicological testing are developed, a lot of effort is invested in finding the most appropriate endpoint, as it is not rare that an organism's response to toxic stress varies depending on the parameter observed [41]. Usually, the most sensitive, ecologically relevant and least variable parameter is preferred and the relative growth rate of a parameter is favored over parameters measured only at the end of the test, since it takes into account the length of the test and makes comparisons between the sensitivity of different species and tests possible [28,45].…”
Section: Additional Growth Parametersmentioning
confidence: 99%
“…This might also hold for Myriophyllum aquaticum growing in mediumonly tests in which a sediment layer is missing (see data in Teodorovi c et al [6]). However, sediment-rooted macrophytes might exhibit linear instead of logistic growth and therefore do not always show a large difference between E r Cx and E b Cx (see data in Tuni c et al [7]). Up to the present, it has not been known whether the E r C50 and the use of an assessment factor of 10 provides sufficient protection in the tier-1 effect assessment for herbicides in general [8].…”
Section: Introductionmentioning
confidence: 99%
“…EC 50 >1 mg/l) (EFSA, 2013). Literature reviewing regarding this topic indicates that better protection goals are reached by this decision since a universally most sensitive species does not exist (Turgut & Fomin, 2002;Teodorović et al, 2012;Tunić et al, 2015;Stevanović et al, 2016). Studies of herbicide effects on outdoor ponds found no direct adverse effect on the invertebrate community, but indicated that long-term changes in macrophyte populations could cause longterm adverse effects on inverbrate community structure (Burdett et al, 2001).…”
Section: Herbicide Effects On Aquatic Organismsmentioning
confidence: 99%